(untitled) (International Journal of Innovative Technologies in Economy, 2020)
This study’s main objective is to analyze the challenges faced by the Republic of Moldova in the economic crisis, which was caused by the COVID 19 pandemic. The vulnerabilities of the Republic of Moldova’s economy and especially its financial system are related mainly to the specifics of the country’s economy, which is small, open, with a continuing current account deficit and a strong subordination to international financial flows. This study’s conclusions consist in the fact that the external risks related to the COVID19 pandemic can be transmitted in the economy of our country through two channels. First, due to uncertain financial conditions in the international economy, difficulties with international financing may arise. Secondly, the vulnerabilities in the economies of the Republic of Moldova’s trading partners will undoubtedly influence the slowdown in exports of goods and services